2020
DOI: 10.1111/and.13948
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine versus antioxidant combination (Antox) and their role in modifying cadmium‐induced testicular injury in adult male albino rats

Abstract: The unfavourable outcome of cadmium (Cd) on male fertility, sex hormones' production and sperm criteria have been reported in literature (Medina et al., 2017). Testicular tissue is particularly susceptible to cadmium-induced damage. Cd causes degeneration of rats' epididymis, seminal vesicles and spermatozoa (Sajjad et al., 2014). Cd, other heavy metals and oestrogenic-based compounds may explain the recent deterioration in male fertility in industrialised regions in the form of sperm count and testicular func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Their study demonstrated that compounds with antioxidant and anti-inflammatory properties could effectively counteract the deleterious effects of cadmium. Uvaria chamae, with its well-documented antioxidant and anti-inflammatory effects [8,10], harmoniously aligns with the findings of Labib and Galal (2020) [7], positioning itself as a promising therapeutic agent at the microscopic level. Furthermore, the microscopic improvements witnessed in the seminal vesicles in the current study supports the outcomes of research conducted by Pamok (2018) [11].…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Their study demonstrated that compounds with antioxidant and anti-inflammatory properties could effectively counteract the deleterious effects of cadmium. Uvaria chamae, with its well-documented antioxidant and anti-inflammatory effects [8,10], harmoniously aligns with the findings of Labib and Galal (2020) [7], positioning itself as a promising therapeutic agent at the microscopic level. Furthermore, the microscopic improvements witnessed in the seminal vesicles in the current study supports the outcomes of research conducted by Pamok (2018) [11].…”
Section: Discussionsupporting
confidence: 64%
“…Our findings gain enhanced significance when juxtaposed against related research. Labib and Galal (2020) [7] explored the realm of natural compounds and their potential to mitigate cadmium-induced reproductive toxicity. Their study demonstrated that compounds with antioxidant and anti-inflammatory properties could effectively counteract the deleterious effects of cadmium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we observed that all evaluated sperm characteristics, including count, viability, motility, and morphology, were significantly superior in the preventive and curative groups compared to the other groups. Numerous studies have highlighted the anti-inflammatory, anticancer, and antioxidant properties of caffeine, even suggesting its potential as a preventative measure against the effects of various drugs and environmental factors on fertility and testicular tissue [ 15 , 31 , 45 , 46 ]. Our findings indicate that caffeine mitigates the tissue damage induced by chronic hyperthermia in testicular tissue.…”
Section: Discussionmentioning
confidence: 99%